Unveiling American (Mis)Conceptions in (Neo-)Orientalist Post 9/11 Fiction: Sherry Jones’s The Jewel of Medina as a Case Study - EL FIDA, Brahim (Integrated Journal for Research in Arts and Humanities, 2023)
Orientalism and its legacies still exercise tremendous influence on how Arabs/Muslims, previously called 'Saracens,' are perceived and represented in different Christian European, then American narratives and contexts. The Prophet Muhammad was targeted to discredit him as 'false' Prophet and and 'ambitious' leader. The Images of sexual potency and debauchery was first addressed to Muhammad, and then trasferred to 'Turks', Arabs and 'Moors'. The continuity of the very images hinder any sincere attempts at mutual understanding. These conceptions are reiterated and reproduced in political discourses and campaigns. They have a negative influence how Islam and Msulisms are conceived and treated. The Jewel of Medina was publsihed in 2008 as a feminist Orientalist attempt to represent and reinterpret early Islamic society and history. The article primarily exposes resilient contemporary misconceptions, images and (mis)representations of Muhammad and Muslims as sexually pervert, cruel, despotic and oppressive. Accordingly, the ‘Orient’ has been widely construed as a luxurious space full of excess. Through reviewing and reconsidering the images and conceptions that were disseminated in European literatures and narratives on Islam and the ‘Orient’ for centuries, the article shows how these very images and depictions are reiterated time and again and consolidated in the Post-Semptember 11th American context and writings.